How Conversational are “Conversational Agents”? Evidence from the Study of Users’ Interaction with a Service Telephone Chatbot - Korbut, Andrei (Social Interaction. Video-Based Studies of Human Sociality, 2023)
The paper considers whether is it possible to view interactions with so-called conversational agents (chatbots, voice assistants, etc.) as a form of conversation. It is argued here that such conversational agents are conversational in a proper sense. To justify this conclusion, the analysis of the beginnings of 100 calls to a Russian municipal call center, processed by a chatbot, is conducted. The revealed features of the inquiry formulations, silences, and overlaps at the beginning of the calls show that users deal with the chatbot as a conversational partner and not as a voice user interface. It is proposed that to call an interaction a “conversation,” it is enough that at least one co-participant (the weak participation requirement) is able to understand all the turns in the interaction (the strong analyzability requirement) as part of the ongoing conversation.